Crustal collapse in the Andean backarc since 2 Ma: Tromen volcanic plateau, Southern Central Andes (36°40′-37°30′S) - Folguera Telichevsky, Andres (2008)
Analysis of seismic lines and gravity data shows the existence of Quaternary extensional depocenters beneath thick covers of < 1 Ma-old volcanic rocks in the Tromen volcanic plateau backarc region (36°40′-37°30′S). Dating and mapping of pre- and post-extensional volcanic units and structure in this area indicate that the main phase of crustal collapse developed during the 1.7-0.7 Ma time interval. However, Late Quaternary reactivations of the extensional structure show that this process is still going on, perhaps with decreasing intensity. Moreover, identification of "mechanical" rift zones and a potentially related main thermal anomaly leads to propose that an east-dipping detachment exists beneath the Late Cretaceous-Late Miocene fold and thrust belt, controlling the crustal collapse at these latitudes. The southernmost Central Andes (35°-37°30′S) have undergone a period of shallow subduction from ~ 13 to ~ 5 Ma, that led to expansion of the arc toward the foreland, generation of ductile-fragile crustal transitions, and subsequent foreland imbrications more than 550 km away from the trench. This framework shifted to a normal Andean subduction type after ~ 5 Ma, and the arc front re-established in the present western position. The consequences of this readjustment were: a) widespread volcanic eruptions of intra-plate melts in the eastern backarc (foreland plateau flows), and b) a major trough formed between the arc front and the foreland plateau basalts (Las Loicas trough). This extensional basin controlled the emplacement of crustal melts as well as primary mantle-derived products, well represented in the Tromen volcanic plateau.